Five hundred leaders of influence. - American Biographical Institute ([Raleigh, N.C.?] : American Biographical Institute, 1993)
"A celebration of global achievements."
Vol. copyrighted 2001 has commemorative edition titled: 1000 leaders of world influence.
SERBIB/SERLOC merged record
Keywords: Biography -- 20th century -- Dictionaries